From the Ground Up A History of Mining in Utah - Whitley, Colleen (University Press of Colorado, 2006)
Despite mining's multidimensional role in the history of Utah since Euro-american settlement, there has never been a book that surveyed and contextualized its impact. From the Ground Up fill that gap with a collection of essays by leading Utah historians and geologists. Essays here address the geology of the state, the economic history of mining in Utah, and the lore of mines and miners. Additionally, the book reviews a handul of particularly significant mineral industries---saline, coal, uranium, and beryllium---and surveys important hard-rock mining regions of the state.